2011
DOI: 10.1103/physrevb.83.174507
|View full text |Cite|
|
Sign up to set email alerts
|

Vortex ratchet reversal: Role of interstitial vortices

Abstract: Triangular arrays of Ni nanotriangles embedded in superconducting Nb films exhibit unexpected dynamical vortex effects. Collective pinning with a vortex-lattice configuration different from the expected fundamental triangular "Abrikosov state" is found. The vortex motion, which prevails against the triangular periodic potential, is produced by channeling effects between triangles. Interstitial vortices coexisting with pinned vortices in this asymmetric potential lead to ratchet reversal, i.e., a dc output volt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
(59 reference statements)
0
18
1
Order By: Relevance
“…Previous experimental and theoretical studies widely showed that rectification signals in superconductors can be generated from a flux-quanta diode effect, i.e., the directional (or ratchet) motion of flux-quanta. For example, rectification was induced in superconducting thin films containing artificial nano-defects with asymmetric geometries [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and in heterostructures containing asymmetrically shaped magnetic nanostructures on top of superconductors [24][25][26][27][28][29][30] . Besides introducing local asymmetries, breaking global inversion symmetries is another way to induce ratchet motion of superconducting vortices.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental and theoretical studies widely showed that rectification signals in superconductors can be generated from a flux-quanta diode effect, i.e., the directional (or ratchet) motion of flux-quanta. For example, rectification was induced in superconducting thin films containing artificial nano-defects with asymmetric geometries [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and in heterostructures containing asymmetrically shaped magnetic nanostructures on top of superconductors [24][25][26][27][28][29][30] . Besides introducing local asymmetries, breaking global inversion symmetries is another way to induce ratchet motion of superconducting vortices.…”
Section: Resultsmentioning
confidence: 99%
“…Whenever a vortex falls inside a hole, the magnetic field in it will experience abrupt jumps. Including holes in the calculations would allow to simulate effects like periodic pinning, to calculate matching fields, as well as the interaction of vortices with defects of different shapes, for example, as is usually done in the context of ratchet effects with triangular defects [11,12].…”
Section: Including Holesmentioning
confidence: 99%
“…Rectification effects of the vortex lattice have attracted a lot of attention, specially in superconducting films with periodic pinning arrays, typically of triangular elements [11,12,13]. In general, nonlinear dynamics in the vortices in asymmetric potentials, under high frequency microwave or combined DC and AC (microwave) drives has recently returned into the focus of interest of the reseachers in vortex physics and applications.…”
Section: Rectification Effectsmentioning
confidence: 99%
“…This effect has been investigated in several systems such as protein motors [2][3][4] , molecular motors [5][6][7] , colloids 8,9 , type II superconducting vortices [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] , electrons 28 , active matter [29][30][31][32] and recently in skyrmions [33][34][35][36][37][38][39] . Reversals of motion from the easy to the hard direction may occur as a function of the applied magnetic field or other variables 12,[17][18][19][40][41][42][43] due to collective interactions between particles. One of the earliest proposals of a two-dimensional (2D) periodic asymmetric potential that can induce a ratchet effect was the asymmetric funnel geometry 20,…”
Section: Introductionmentioning
confidence: 99%